2003
DOI: 10.1093/carcin/24.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Response of human mammary epithelial cells to DNA damage induced by BPDE: involvement of novel regulatory pathways

Abstract: The responses of a line of normal human mammary epithelial cells, HME87, to treatment with the ultimate carcinogen benzo[a]pyrene diol epoxide (BPDE) were analyzed using a directed gene expression analysis technique, RAGE. Under conditions where cell number was decreased by 50% 24 or 48 h post-treatment, flow cytometry demonstrated no establishment of a G(1)/S arrest nor induction of apoptosis; cells continued to enter S phase from G(1) for at least 24 h but were blocked at G(2)/M. Using the RAGE technique, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 64 publications
4
33
1
Order By: Relevance
“…The XPC protein recognizes a variety of bulky DNA damages including UV-caused cyclobutane pyrimidine dimers and cisplatin-generated interstrand crosslinks (ICL) [9][10][11][12][13][14][15][16]. The XPC protein binds tightly with an HR23B protein to form a stable XPC-HR23B complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The XPC protein recognizes a variety of bulky DNA damages including UV-caused cyclobutane pyrimidine dimers and cisplatin-generated interstrand crosslinks (ICL) [9][10][11][12][13][14][15][16]. The XPC protein binds tightly with an HR23B protein to form a stable XPC-HR23B complex [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cell cycle phases showed an accumulation of cells in the G1 and G2 phase after B[a]P exposure (Vaziri et al, 1997;Zhu et al, 2005). It has also been shown that BPDE, the metabolite of B[a]P, can induce a G2/M accumulation (Wang et al, 2003). In line with these findings, G1-S arrest was observed in testis of B[a]P exposed male mice (Verhofstad et al, 2010).…”
Section: Apoptosis and Cell Cyclesupporting
confidence: 61%
“…Moreover, there is emerging evidence that indicates that human mammary epithelium may be susceptible to carcinogenic transformation upon exposure to BPDE (Mei et al, 2003). For instance, human mammary epithelial cells and breast cancer cell lines, exposed to BPDE, exhibited altered cell cycle progression, decreased BRCA-1 expression and an increased spectrum of p53 mutations (Jeffy et al, 2002;Pfeifer et al, 2002;Wang et al, 2003;Burdick et al, 2006). It has also been shown that treating MCF 10A cells with 1 mM of B[a]P for 48 hours is sufficient to cause chromosomal aberrations and induce anchorageindependent growth (Caruso et al, 2001).…”
Section: Introductionmentioning
confidence: 99%